Brain asymmetries and handedness in the specimens from the Sima de los Huesos site (Atapuerca, Spain). (17th March 2017) - Poza-Rey, Eva María; Lozano, Marina; Arsuaga, Juan Luis
Abstract: This study investigates handedness in a group of individuals from the Sima de los Huesos site (Atapuerca, Spain). In this research, handedness has been studied by analyzing the brain endocast asymmetries (cerebral evidence), and the results (the assignment, of the manual preference in each individual) have been compared to previous results from the determination of handedness from labial striations on the anterior dentition in the same individuals. From the dental analysis, all individuals from SH were right-handed. After combining the results of both studies, 4 individuals could be analyzed in depth. In 3 of these individuals, the assignment of probable handedness was coincident. The results did not coincide in just 1 individual (Cranium 6). In this specimen, labial striations indicated a right oblique orientation consistent with right-handedness, but this was not consistent with our results from the endocast analysis. The existence of some pathology in the natural skilled hand, learning by imitation from right-handers, or ambidextrous handedness are some of the interpretations derived from this special case.